Immunhisztokémiai, immuncitokémiai és elektronmikroszkópos vizsgálatok kísérletes E. coli pyelonephritisben [Immunohistochemical, immunocytochemical and electron microscope studies in experimental E. coli pyelonephritis]. - Iványi Béla (MORPHOLÓGIAI ÉS IGAZSÁGÜGYI ORVOSI SZEMLE, 1989)
Authors have studied in apostematous pyelonephritis induced by the ligation of the ureter and the intravenous injection of E coli bacteria the localization and elimination with time of the pathogen. The pathogen was demonstrated by light and electron microscopy, its parietel antigen was localized with the light microscopic peroxidase antiperoxidase and post-embedding electron microscopic immunogold techniques. Two days after inoculation the suppurative inflammation of tubulo-interstitial foci was observed; in the capillaries, interstitium, and tubuli, free and phagocyted bacteria were encountered. In the interstitium, in the proximal tubuli and in the capillary space of some glomeruli bacterial groups were observed. Intracapillary bacteria were attached by their outer wall to the surface of endothelial cells. In the tubuli this adherence occurred with pili or with the outer layer of bacterial wall. From the seventh day after inoculation macrophages containing PAS-positive globuli appeared in the interstitium. Under the electron microscope these globuli proved to be features composed of myelin figures of phagolysosomal origin. Globuli and the myelin figures possessed an E. coli antigenicity. Thirteen weeks after inoculation E. coli antigen positivity was found in the cytoplasm of inflammatory cells in the tubular walls and in the suppurative cylinders, The organism was apparently unable to eliminate the materials derived from the pathogenic microorganisms.